Strategi Ketepatan Penyaluran Zakat Produktif dalam Meningkatkan Usaha Idan Kesejahteraan Ekonomi Mustahik Idi Baznas Purbalingga - Novarianti, Siti; Suyuti, Muh Hikamudin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The distribution of productive zakat at BAZNAS Purbalingga is carried out through a systematic strategy, including mapping mustahik needs, entrepreneurship training, and periodic monitoring and evaluation. The mapping was carried out by direct surveys and coordination with the village government to ensure that assistance was given on target. After that, mustahik was given entrepreneurship training so that they had skills in managing business and finance. Monitoring and evaluation are carried out to ensure the effectiveness of the program and its impact on the mustahik economy. The results of the study show that productive zakat recipients experience an average income increase of 40% and a reduced dependence on social assistance. In addition, the selection mechanism through the productive zakat application form helps increase transparency and accountability in the distribution of funds. With good governance, productive zakat can be an instrument of sustainable economic empowerment for the community.